Empirical DFT Model to Predict Triplet Quantum Yield Through Singlet Oxygen Yields. Issue 3 (5th January 2022) - Steinkamp, Bret A.; Lutkus, Luke V.; Lewis, Rob; McCormick, Theresa M.
Abstract: Triplet photosensitizers can be used for a variety of applications, including photocatalysis, OLEDs, and photodynamic therapy. Excited triplet states can be quenched by triplet oxygen to make singlet oxygen. Often the singlet oxygen quantum yield (Φ▵ ) is used as a lower approximation for the triplet yield. Unpredictable effects of even minor structural changes can drastically alter the Φ▵ and complicate the design of new triplet photosensitizers. The most common strategy to increase Φ▵ is to incorporate heavy atoms, promoting the "heavy atom effect". However, the position and the identity of the heavy atom greatly influences the Φ▵ . We have created a predictive model that correlates calculated natural atomic orbital composition of the heavy atom(s) contributing to the frontier molecule orbitals of a photosensitizer with the experimental Φ▵ . The model, derived from several fluorescein derivatives, provides a calculated Φ▵ in agreement with the experimental values for a variety of well‐known photosensitizers, including rhodamine dyes, fluorescein derivatives, and octahedral metal complexes. Abstract : Predictive model : A simple DFT based model that can be used to predict triplet yields has been tested against a variety of chromophores including rhodamine dyes, fluorescein derivatives, and octahedral metal complexes.